2022
DOI: 10.1111/conl.12901
|View full text |Cite
|
Sign up to set email alerts
|

How can the European Common Agricultural Policy help halt biodiversity loss? Recommendations by over 300 experts

Abstract: The European Union's Common Agricultural Policy (CAP) has not halted farmland biodiversity loss. The CAP post-2023 has a new ''Green Architec-This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 66 publications
(37 citation statements)
references
References 25 publications
0
21
0
1
Order By: Relevance
“…The European Union’s new (2023–2027) Common Agricultural Policy (CAP) aims to reverse current environmental degradation and biodiversity declines in European farmland 1 through the achievement of three green objectives: contribute to climate change mitigation, support efficient natural resource management, and reverse biodiversity loss 2 , 3 . Following the outbreak of war in Ukraine, the European Commission proposed a series of short and medium-term relaxations to CAP’s environmental commitments to offset expected shortages in grain imports and enhance food security 4 .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…The European Union’s new (2023–2027) Common Agricultural Policy (CAP) aims to reverse current environmental degradation and biodiversity declines in European farmland 1 through the achievement of three green objectives: contribute to climate change mitigation, support efficient natural resource management, and reverse biodiversity loss 2 , 3 . Following the outbreak of war in Ukraine, the European Commission proposed a series of short and medium-term relaxations to CAP’s environmental commitments to offset expected shortages in grain imports and enhance food security 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, cultivating semi-natural habitats like long-term or unploughed annual fallows will have serious environmental costs, including an increase in pesticide and fertiliser application, since fallows often occupy less productive land 13 . Even a moderate increase in food production at the expense of the semi-natural habitats remaining in farmland landscapes (field margins, grasslands, and fallow land), which support most of Europe’s farmland biodiversity and its associated ecosystem services 14 , will seriously damage farmland biodiversity and sustainability in European agricultural landscapes 3 , 15 . For example, a comprehensive study carried out on 169 farms across 10 European countries showed that semi-natural habitats, including fallows, occupied 23% of the land but hosted 49% of vascular plant, earthworm, spider, and wild bee species; a 10% decrease of these habitats if reclaimed for food production would cause exponential decreases in biodiversity, but only moderate linear increases in production 15 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Within those two instruments, Member States will decide how to allocate funding for voluntary measures tailored to meet their own specific needs (European Commission, 2020a). The approved CAP reform aims to reflect the Green Deal objectives, but substantial flaws in the design of its mechanisms raise doubts about the effectiveness of resource allocation to achieve the environmental commitments (Pe'er et al, 2021). Here we present the challenges that the approved CAP faces to fulfil its sustainability ambitions, and the opportunities it provides for Member States to improve their environmental performance, with the aim of successfully integrating with the Green Deal mandate.…”
Section: Introductionmentioning
confidence: 98%